THE EFFECT OF TEACHER'S TEACHING SKILLS ON ACADEMIC AND NON-ACADEMIC ACHIEVEMENTS OF STUDENTS OF SD NEGERI 1 BATUR, BANJARNEGARA REGENCY - Sulastri Sulastri (Universitas PGRI Yogyakarta, 2022)
This study aimed to analyze the effect of teacher teaching skills on students' academic and non-academic achievement. This type of research is a quantitative description and analyzed using SPSS 22 software. The method in this research is a survey using a questionnaire. This research shows a positive and significant effect between teacher teaching skills on student academic achievement as evidenced by t count 2.52 with a probability of 0.015 < 0.05. The relationship between students' learning motivation and non-academic achievement showed a positive and significant effect with an at-count of 3.397 with a probability value of 0.01 <0.05. The relationship between teacher teaching skills through student motivation on non-academic achievement also shows a positive and significant effect. Teachers' teaching skills have a significant value of 0.012 and students' learning motivation of 0.01, which shows a value of <0.05. The analysis results show that teacher teaching skills through student motivation on non-academic achievement is 26.9%, while other factors outside this research model influence the rest.